Erythropoietin and Its Angiogenic Activity - Kimáková, Patrícia (Int J Mol Sci, 2017)
Erythropoietin (EPO) is the main hematopoietic hormone acting on progenitor red blood cells via stimulation of cell growth, differentiation, and anti-apoptosis. However, its receptor (EPOR) is also expressed in various non-hematopoietic tissues, including endothelium. EPO is a pleiotropic growth factor that exhibits growth stimulation and cell/tissue protection on numerous cells and tissues. In this article we review the angiogenesis potential of EPO on endothelial cells in heart, brain, and leg ischemia, as well as its role in retinopathy protection and tumor promotion. Furthermore, the effect of EPO on bone marrow and adipose tissue is also discussed.